The mathematics education of elementary teachers : issues and strategies for content courses - Hart, Lynn Cecilia, 1948-; Oesterie, Susan; Auslander, Susan Swars; Kajander, Ann (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
This book is an edited volume addressing specific issues of significance for individuals involved with the undergraduate mathematics content preparation of prospective elementary teachers (PSTs). Teaching mathematics content courses to this group of students presents unique challenges. While some PSTs enter their teacher preparation with weak mathematical skills and knowledge, many also hold negative attitudes, anxiety, and misguided beliefs about mathematics. This book is designed to support instructors who teach these students in mathematics content for elementary teachers courses.Elementary teachers need a richly developed understanding of the mathematics they are teaching in order to teach it effectively. Providing them with the needed preparation is difficult, but can be eased with a solid understanding of the mathematical concerns and limitations PSTs bring to the learning of mathematics and a familiarity with the standards and curricula topics PSTs will be expected to teach. Chapter One makes the argument that elementary mathematics is not trivial. This is followed by an analysis of four central issues related to the mathematical preparation of elementary teachers, specifically: (1) selecting/creating/modifying and implementing mathematical tasks (2) noticing/understanding children's ways of thinking as a foundation for learning mathematics, (3) developing mathematical habits of mind in PSTs, and (4) understanding the role affect plays in the mathematical learning of PSTs. The final chapter presents three international examples of programs that currently consider these factors in the implementation of their courses.